The Efficacy of Emotion Regulation Skills in Patients with Irritable Bowel Syndrome: Reduction of Psychopathological Symptoms, Emotion Regulation Problems and Improvement in Quality of Life: a case series - Doroui, Nadia; Sadeghi, Kheirollah; Foroughi, Ali Akbar; Ahmadi, Seyed Mojtaba; Parvizi Fard, Ali Akbar (International Journal of Applied Behavioral Sciences, 2017)
Background and Purpose: Emotion regulation therapy (ERT) is one of the third wave of cognitive behavioral therapies which address patients’ problem by improving four emotion regulation skills (i.e. mindfulness, allowing or acceptance, distance, and reappraisal). ERT could be applied for disorders with strong emotional element. Therefore, this study aims to determine the efficacy of emotion regulation skills on reduction of psychopathological symptoms, difficulty of emotion regulation and improvement of quality of life in patients with irritable bowel syndrome (IBS). Method: In an experimental single-case design of baseline type, 5 patients with irritable bowel syndrome (IBS) were included in the therapy process after they satisfied necessary condition. The patients had 9 sessions therapy (i.e. 90 minutes). In order to evaluate efficacy of the therapy, the measures of Depression Anxiety Stress Scale (DASS-21), Difficulty in Emotion Regulation Scale (DERS) and Irritable Bowel Syndrome Quality Of Life (IBS-QOL34) were used. To analyze the collected data, certain diagrams, reliable change index, improvement percentage, and corrected size effect (i.e. Hedges’ g) were used. Findings: The emotion regulation therapy reduced the psychopathological symptoms, difficulty of emotion regulation and increase of quality of life in patients with IBS. Total percentages of improvement of anxiety, depression, difficulty of emotion regulation and quality of life were 32.25, 34.68, 40.21 and 58.44 percent respectively. Conclusion: The ERT reduced psychopathological symptoms and difficulty of emotion regulation and improved quality of life in patients with irritable bowel syndrome significantly. Consequently, therapists seem to be able to use the skills of this treatment to reduce the psychological problems of these patients.